Can better governance quality handle inequality in the digital age? Emprical evidence from developing economies - Ho Thu, Hoai; Ho Thi, Lam; Le Hong, Ngoc (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study investigates the relationship between digitalization and income inequality, with a particular focus on the moderating effect of governance quality in 44 developing countries over the period 2002–2023. Employing the System Generalized Method of Moments (System GMM) and the Pooled Mean Group (PMG) estimation techniques, the findings indicate that digitalization has a significant influence on income inequality. Specifically, digitalization appears to contribute to reducing income disparities, suggesting its potential as a strategic tool for poverty alleviation and the advancement of the Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty) and SDG 10 (Reduced Inequalities). Additionally, the results demonstrate that governance quality exerts a mitigating effect on income inequality within the context of digital transformation. However, the study also highlights that in institutional environments where market efficiency is prioritized over equitable distribution, the capacity of governance to reduce inequality may be constrained. These findings underscore the necessity of adopting inclusive digital policies and equity-oriented growth strategies to address the institutional “digital bias” and ensure that the benefits of digitalization are distributed more equitably in developing economies.